THE UNIQUENESS OF ISLAMIC EDUCATION IN INDONESIA - Dindin Jamaluddin (Jurnal Isema : Islamic Educational Management, 2017)
Islamic education, the oldest education system in Indonesia which is admitted and appreciated for its contribution to the nation building, emerged together with the arrival of Islam to Indonesia, even before the Dutch’s occupation. Afterward, it took its own path, independent of government, clung to its own way and opened to change in that tradition. Islamic religious education institutions called pesantren Initially used the Arabic language as teaching media. When the desire to develop a system of public education for all people at the turn of the 20th century grew, several prominents thougth to look for possibilities to engage in the development of Islamic education. Among the prominent Muslim scholars are K.H. Ahmad Dahlan and K.H. Hashim Asy'ari who initiated to establish Islamic modern schools called madrasahs in many areas. Education in Islamic Schools has become a tool of struggle to achieve independence and freedom in Indonesia. Pesantren which is a model of Islamic education indoctrinated his students to believe that colonialism was a wrong and and they are created diffrently not to invade one another but to live in harmony. That’s why Dutch colonial government refused to subsidize the model of Islamic education in schools because it was considered of no use and will threaten the authority and dignity of the Dutch government.Key Words: Uniqueness Of Islamic, Indonesia.